The Effectiveness of Listening Team Learning Strategies to Improve the Results of class five in Fiqh Lesson at Islamic Boarding School Darussalam Gontor 2 for Female - Zarkasyi, Ahmad Hidayatullah; Solihah, Dwi Aprilia; Khoiriyah, Dini Rofiatul (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2023)
Listening Team Strategy cooperative learning model that requires students to think critically, and each group has a different task. So, students can play an active role in expressing their opinions. The low average result in fiqh lesson (bidayatul mujtahid) of class five in Fiqh lesson (Bidayatul Mujtahid) of Islamic Boarding School Darussalam Gontor 2 for female shows that students do not understand the material as whole. Based on the description above, this research aims to: (1) Know the result before and after using the methode from Listening Team in strategy for the experimental class and (2) know the result before and after using conventional learning in the control class (3) to know the effectiveness of listening team strategy on learning outcomes  (Bidayatul Mujtahid) of class five in Fiqh lesson at Islamic Boarding School Darussalam Gontor 2 for female. The type of research in this study is quantitative experiments using a quasi-experiment design, namely a nonequivalent control group design with the form of a pretest-posttest control group design. Test the initial and final tests in both classes. Based on the results of this study, researchers concluded that the Listening Team strategy effected to increase the learning outcomes of class five of Islamic teacher training college. Researchers hope that further research to deepen the learning tractor and improve student outcomes. It can help students to understand learning material, especially fiqh lesson.